2002
DOI: 10.1080/00480169.2002.36293
|View full text |Cite
|
Sign up to set email alerts
|

Administration of pregnant mare serum gonadotropin to Japanese quail (Coturnix coturnix japonica): dose response over seven days and comparison of delivery by daily injection or osmotic pump

Abstract: A dose of 10 IU PMSG/day was chosen for use in future experiments with Japanese quail, for the first 7 days of treatment. The delivery method of choice for future studies will depend on the practical considerations of the research in question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…19 These pumps have been used in laboratory and research settings in avian species. 20,21 One of the authors (JMS) of the study reported here has used these pumps in clinical settings to deliver antimicrobials to primates a and snakes 22,b and to provide postoperative analgesia to exotic felids on the basis of a study in domestic cats. 23 To our knowledge, no clinical application of these pumps in avian species has been reported.…”
Section: CLmentioning
confidence: 99%
“…19 These pumps have been used in laboratory and research settings in avian species. 20,21 One of the authors (JMS) of the study reported here has used these pumps in clinical settings to deliver antimicrobials to primates a and snakes 22,b and to provide postoperative analgesia to exotic felids on the basis of a study in domestic cats. 23 To our knowledge, no clinical application of these pumps in avian species has been reported.…”
Section: CLmentioning
confidence: 99%